Side of Lesions Predicts Surgical Outcomes in Patients With Drug-Resistant Temporal Lobe Epilepsy Secondary to Focal Cortical Dysplasia Type IIIa - He, Xinghui; Liu, Dingyang; Yang, Zhuanyi; Zhang, Junmei; Li, Sushan; Yang, Zhiquan (Frontiers in Neurology, 2020)
Objective: This study aims to evaluate the surgical outcomes and analyze the predictors of surgical outcomes in patients undergoing anterior temporal lobectomy (ATL) for drug-resistant temporal lobe epilepsy (TLE) secondary to focal cortical dysplasia (FCD) type IIIa Methods: Data on patients with drug-resistant TLE secondary to FCD type IIIa who had undergone ATL at Xiangya Hospital, Central South University from January 2014 to April 2018, were collected retrospectively. International League Against Epilepsy (ILAE) classification was used to evaluate postoperative seizure outcomes. Predictors of surgical outcomes were identified by using univariate and multivariate analyses. Results: A total of 43 patients with drug-resistant TLE secondary to FCD type IIIa who had undergone ATL were included in this study. Twenty patients had right ATL, and 23 patients had left ATL. With a follow-up of 2 to 6 years, 76.7% (33 of 43) of patients were seizure-free. Univariate and multivariate analysis results indicated that lesions on the right side independently predict postoperative seizure freedom (OR,0.08; 95% CI, 0.01-0.72; P=0.024). Conclusion: ATL is an effective therapy for patients with drug-resistant TLE secondary to FCD type IIIa. Patients with lesions on the right side are more likely to achieve postoperative seizure freedom.